Feasibility of vagus nerve modulation (VNMM/taVNS) in cognitive-swallowing dual-task paradigms: a fNIRS pilot study - Zhiyong Wang; Zhiyong Wang; Keling Cheng; Junhui Bai; Cuicui Zhang; Jun Ni; Jun Ni (Frontiers in Neuroscience)
BackgroundNon-invasive vagus nerve stimulation techniques show promise for modulating cortical networks, but their comparative effects during combined cognitive-swallowing tasks remain underexplored.AimsThis feasibility study aimed to: (1) establish a protocol for assessing transauricular vagus nerve stimulation (taVNS) and VNMM effects using fNIRS during dual-task paradigms, and (2) compare their impacts on cortical activation and functional connectivity.MethodsThis protocol (ChiCTR2200065698) consisted of two separate blocks, a cognitive task (n = 25) and a swallowing task (n = 25), and healthy subjects in either block were randomly assigned to the taVNS and VNMM groups. The subjects underwent swallowing or cognitive task-state data acquisition before and after the trial intervention. The functional near-infrared spectroscopy (fNIRS) data were analyzed by generalized linear modeling (GLM) and seed-based correlation analysis to assess the cortical excitability and brain connectivity, and a BrainNet Viewer was used to visualize the intervention effects.ResultsUnder the cognitive and swallowing task-state fNIRS protocols, both taVNS and VNMM significantly enhanced the activation effects and intra/inter-hemispheric brain network connectivity in the cognitive or swallowing-related brain regions (p < 0.05).ConclusionsThis study demonstrates the feasibility of using fNIRS to differentiate taVNS/VNMM effects during dual-task paradigms. Preliminary data suggest VNMM may offer superior network modulation, warranting larger trials to validate behavioral correlates.Clinical trial registrationChictr.org.cn, identifier: ChiCTR2200065698.